Kewenangan Mahkamah Konstitusi Republik Indonesia Mengadili Perselisihan Hasil Pemilukada - Desak Made Widi Antari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe Article 157 of Law Number 10 Year 2016 authorizes the Constitutional Court to resolve the dispute over the regional head election results quarrel before a special court of election is formed. The authority of the Constitutional Court is limited by the provisions of Article 158 of the Act. Consequently, only disputes on election results that meet the threshold of the vote that has a legal standing to be able to file a lawsuit to the Constitutional Court. The restriction in Article 158 leaves many parties with the view that the Constitutional Court fails to become an institution capable of safeguarding the Constitutional Rights of Citizens and Article 158 provides an opportunity for candidates to commit significant violations in order to maintain the threshold of the vote.